1993
DOI: 10.1007/bf02546638
|View full text |Cite
|
Sign up to set email alerts
|

Degradation behaviour of polymeric materials found in auto Shredder residue wastes

Abstract: The therrnogravimetry of a series of 50/50 mixtures of polypropylene, acrylonitrile/butadiene/styrene, polyvinyl chloride and polyurethane polymers have been studied as representative of the major polymeric materials found in automobile shredder residues. The weight loss behaviour of these polymeric mixes have been compared with the results calculated from the individual polymeric components. This comparison of the thermogravimetry curves and the calculated kinetic parameters indicates that interactions occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Similar findings have been reported by Day et al [41,42] who studied ABS, PP, PVC and PU mixtures and observed changes in the DTG peak temperatures and shapes. Day et al [43] stated that both diffusion and chemical interactions are possible for binary plastic mixtures.…”
Section: Polymer Mixturessupporting
confidence: 85%
“…Similar findings have been reported by Day et al [41,42] who studied ABS, PP, PVC and PU mixtures and observed changes in the DTG peak temperatures and shapes. Day et al [43] stated that both diffusion and chemical interactions are possible for binary plastic mixtures.…”
Section: Polymer Mixturessupporting
confidence: 85%
“…Peak #1 at about 250~ however appears to be due to some other material which need not be polymeric such as engine oil, lubricants, etc. However, in a previous study we have shown that binary mixtures of these polymers can result in interactions causing changes in peak temperatures [11]. In this earlier study we compared experimental and calculated information and noted that interactions occurred in the degradation of mixed polymeric components.…”
Section: Peak Identificationmentioning
confidence: 95%
“…The kinetics of the thermal dehydrochlorination of PVC has been extensively studied in literature using both isothermal and linear heating rate methods [12,13,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. It is striking the very broad dispersion of results in terms of kinetic parameters reported in these papers.…”
Section: Introductionmentioning
confidence: 99%
“…It is striking the very broad dispersion of results in terms of kinetic parameters reported in these papers. Most of the kinetic studies of thermal dehydrochlorination of PVC assume an n order kinetic model for the analysis [12,13,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][58][59][60][61][62]. Additionally, some authors have used a more complex approach by proposing either two consecutive [8,13,50] or two competitive [49] n order kinetic models.…”
Section: Introductionmentioning
confidence: 99%